2009
DOI: 10.1128/jcm.02475-08
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Human Infection with Salmonella enterica Serovar Apapa Resulting from Exposure to a Pet Lizard

Abstract: We present the first documented human case of Salmonella enterica serovar Apapa infection, isolated concurrently from a hospital inpatient and a pet lizard. The isolates were identical by biochemical profiling and pulsed-field gel electrophoresis. This rare serotype is known to be associated with reptiles. The current practice for avoiding reptile-associated infections is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Salmonella Apapa has previously been reported as a pathogen in pet reptileassociated human infections. 16,21, 41 Pees et al 41 recently demonstrated that most of the reptileassociated infections in children in Germany during 2010-2011 were not associated with the Salmonella serovars commonly related to human salmonellosis. Those authors concluded that, currently, no specific serovar seemed to be of particular zoonotic importance and, accordingly, that all Salmonella strains found in reptiles should be considered potentially infectious to children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella Apapa has previously been reported as a pathogen in pet reptileassociated human infections. 16,21, 41 Pees et al 41 recently demonstrated that most of the reptileassociated infections in children in Germany during 2010-2011 were not associated with the Salmonella serovars commonly related to human salmonellosis. Those authors concluded that, currently, no specific serovar seemed to be of particular zoonotic importance and, accordingly, that all Salmonella strains found in reptiles should be considered potentially infectious to children.…”
Section: Discussionmentioning
confidence: 99%
“…We would add that, in this context, the rarely occurring serovars should not be overlooked. In addition to the S. e. enterica subspecies, S. e. houtenae, S. e. arizonae, S. e. diarizonae, and S. e. salamae have also been described as causative agents in human infections associated with direct or indirect contact with pet reptiles 1,16,19,21,48 Interestingly, in a Swiss study, Overesch et al 38 found that none of the isolates from snakes belonged to S. e. enterica and that most of the isolates from lizards also belonged to subspecies other than S. e. enterica, while most isolates from chelonians did belong to S. e. enterica. This is similar to the patterns found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotype Adelaide has been cultured from poultry, Rubislaw has been found in food products ranging from black pepper to meat and fish, and Oslo appears most common in humans, but has also been detected in cockroaches (Chmel and Armstrong 1976;Onderka and Finlayson 1985;Devi and Murray 1991;Centers for Disease Control and Prevention 2008). Serotypes Houten, Apapa, and Salmonella enterica subspecies arizonae are more commonly associated with reptiles, but have been reported to cause salmonellosis in humans (Sanyal et al 1997;Woodard et al 1997;Willis et al 2002;Cooke et al 2009;Haase et al 2011). Many reptile-associated serotypes reported in previous cases of human salmonellosis in the U.S. were not identified in this study, including Salmonella serotypes Nima, Paona, Sandiego, St. Paul, Tennessee, Typhimurium, IV 44:z 4 z 23 :-, and IV 48:g,z 51 :-(formerly S. Marina) (Mermin et al 1997;Levy et al 1999;Reporter et al 2003;Weiss et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Reptiles are often asymptomatic carriers of some important pathogenic bacteria [3][4][5]. In particular, several studies showed that cold-blooded animals are direct or indirect source of salmonellae in human infection outbreaks [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%